On three new species of the earthworm genus Drawida Michaelsen, 1900 (Clitellata: Moniligastridae) from south-western India - Narayanan, S. Prasanth; Jose, Divya; C., Bijoy; Kurien, Vijo Thomas; Thomas, A.p. (Zootaxa, 2024)
Three new earthworm species of the genus Drawida Michaelsen, 1900, namely D. jatinderi Narayanan, sp. nov., D. paliwali Narayanan, sp. nov. and D. proboscidea Narayanan, sp. nov., are described from materials collected from the Kerala state of south-western India. D. jatinderi Narayanan, sp. nov., belongs to D. travancorensis Michaelsen, 1910 species group, characterized by spermathecal pores at C setal line, male pores at mid bc setal lines, glandular prostate, spermathecal atrium present, dorsal pores, and genital markings absent. Whereas D. paliwali Narayanan, sp. nov., and D. proboscidea Narayanan, sp. nov. belong to the D. robusta robusta (Bourne, 1886) group, characterized by glandular prostates and bilobed spermathecal atria. D. jatinderi Narayanan, sp. nov., and D. proboscidea Narayanan, sp. nov. were collected from the midlands of Ernakulam district, and D. paliwali Narayanan, sp. nov., was collected from the higher altitude evergreen forest of the Parambikulam Tiger Reserve of Palakkad district. Here we provide a detailed description of the external and internal characteristics of the new species, along with illustrations of the key characters. With the new findings, a total of 52 Drawida species are known from the Western Ghats biodiversity hotspot.